2021
DOI: 10.3389/feduc.2021.667918
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Student Success and Persistence in STEM With Active Learning Approaches in Emerging Scholars Classrooms

Abstract: Over the last several decades, Emerging Scholars Programs (ESPs) have incorporated active learning strategies and challenging problems into collegiate mathematics, resulting in students, underrepresented minority (URM) students in particular, earning at least half of a letter grade higher than other students in Calculus. In 2009, West Virginia University (WVU) adapted ESP models for use in Calculus I in an effort to support the success and retention of URM STEM students by embedding group and inquiry-based lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Additionally, since many students at risk of non-matriculation are traditionally in underrepresented groups, including students of color and those who identify as female, enhancing performance through active learning modules and other supplemental materials can lead to not only their success but also a more diversified STEM field. Similarly, studies have demonstrated that incorporating active learning within curricula can level the playing field by enhancing the performance of underrepresented students and the inclusivity of courses (Miller et al, 2021;Theobald et al, 2020). While the study in this article highlights improving academic success and providing support for autonomy, other studies have identified how active learning can enhance the community aspect of courses, enhancing the learning experience for participants (Ricks et al, 2014).…”
Section: Research Questionsmentioning
confidence: 81%
See 1 more Smart Citation
“…Additionally, since many students at risk of non-matriculation are traditionally in underrepresented groups, including students of color and those who identify as female, enhancing performance through active learning modules and other supplemental materials can lead to not only their success but also a more diversified STEM field. Similarly, studies have demonstrated that incorporating active learning within curricula can level the playing field by enhancing the performance of underrepresented students and the inclusivity of courses (Miller et al, 2021;Theobald et al, 2020). While the study in this article highlights improving academic success and providing support for autonomy, other studies have identified how active learning can enhance the community aspect of courses, enhancing the learning experience for participants (Ricks et al, 2014).…”
Section: Research Questionsmentioning
confidence: 81%
“…According to Ricks et al (2014) and Theobald et al (2020), active learning modules provide a flexible avenue for accessing content and using course time as a collaborative time to practice the application of course content. Active learning can increase students' final course grades in classes aside from engineering, such as in Calculus courses (Miller et al, 2021) and can also narrow achievement gaps in passing rates of underrepresented students (Theobald et al, 2020). Utilizing active learning can support students' interaction with course content while also providing a social system through collaboration, therefore allowing for an increase in retention as discussed by Xu (2016).…”
Section: Research Questionsmentioning
confidence: 99%
“…As a result, it is important to discuss strategies that promote student confidence in chemistry classrooms. In general, evidence-based instruction practices, such as student-centered instruction and active learning, have been identified as beneficial for STEM students with regard to their self-efficacy and retention in STEM programs. Active learning especially might have been difficult to implement in remote and hybrid learning environments and will be critical with the return to face-to-face instruction in addition to other practices that promote self-efficacy, such as undergraduate research experiences and student mentorship programs. , …”
Section: Discussionmentioning
confidence: 99%
“…Next, Miller et al (2021) in his study has made a difference between the two groups that use AL and also traditional learning. The results of the test were found to be better for the group that practiced AL, with a relatively large difference in achievement between the two groups.…”
Section: Active Learning and Student Achievementmentioning
confidence: 99%